The poverty alleviation program in A Tsunami impacted area: Models PKH and BPNT Indonesia - Ciptawaty, Ukhti; Ambya, Ambya; Nairobi, Nairobi; Suparta, I Wayan; Djayasinga, Marselina; Wahyudi, Heru (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the overall effectiveness of Program Keluarga Harapan (PKH) and Bantuan Pangan Non-Tunai (BPNT) in reducing poverty in Aceh Province, Indonesia, a province heavily affected by the 2004 tsunami disaster. Using a 23-year time series (2000-2022) dataset and a threshold regression model, the study investigates the effects of such social assistance programs on the alleviation of poverty (per capita income and poverty line). This study highlights some important challenges to improvement in program implementation, such as inefficiencies in the distribution of funds, socio-cultural barriers, and limited alignment with broader economic strategies. The study opens with a discussion of the Indonesian government’s Household Welfare Improvement program, a conditional cash transfer program designed to reduce poverty and improve health, nutrition, and education. Based on the evidence obtained, the authors recommend improvements to PKH, including increases in budget allocation, tailored economic empowerment processes, and enhanced program structure in order to maximize the program’s long-term poverty reduction impact. The study recommends optimizing food distribution and diversification of food assistance to meet local needs for BPNT. By shedding light on the specific mechanisms driving these effects, these findings add to the existing body of evidence regarding the impact of social welfare policies and provide insights that could inform future programs aimed at improving the effectiveness of assistance to impoverished regions in the aftermath of disasters or natural hazards.